Pengaruh Nilai Sosial dan Norma Hukum terhadap Pembentukan Konstitusi di Indonesia - Rihadatul’aisy, Najwa; Adezira, Rangga (Media Hukum Indonesia (MHI), 2025)
This study discusses how social values and legal norms influence the formation and development of the Indonesian constitution. Using a literature study method and a descriptive-qualitative approach, this study analyzes various secondary sources published between 2019 and 2024. The results of the study show that Pancasila, as the main social value, has been institutionalized into the national legal system and has become the philosophical basis for the development of the constitution. Meanwhile, legal norms play an important role in forming the formal structure of the state and maintaining the legitimacy of state institutions. From the time of its formulation to the amendments in the contemporary era, the Indonesian constitution shows a dynamic relationship between the ever-growing social aspirations and the need for legal certainty. Thus, the formation of the Indonesian constitution can be understood as the result of a dialogue between social reality and the formal legal process based on the values of Pancasila.